THE BURDEN OF VESICO-VAGINAL FISTULA IN ILE-IFE, SOUTH WESTERN NIGERIA - Akintunde Olusegun Fehintola; Olusegun O Badejoko; Adebimpe O Ijarotimi; Babatola Bakare; Funmito O Fehintola; Adebanjo B Adeyemi (Sanamed, 2017)
Background: Vesicovaginal fistula is a major cause of severe morbidity and potential mortality, which can result in marital disruption, rejection, and eventual destitution.